2002
DOI: 10.1637/0005-2086(2002)046[0497:acoaia]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Aspergillosis in a Broiler Breeder Flock

Abstract: A case of aspergillosis in a broiler breeder flock having respiratory and nervous system problems caused by Aspergillus fumigatus and Aspergillus niger is documented. Dyspnea, hyperpnea, blindness, torticollis, lack of equilibrium, and stunting were observed clinically. On postmortem examination of the affected birds, white to yellow caseous nodules were observed on lungs, thoracic air sacs, eyes, and cerebellum. Histopathologic examination of lungs and cerebellum revealed classic granulomatous inflammation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 13 publications
7
55
1
3
Order By: Relevance
“…Removal of mouldy litter resulted in health improvement [16]. The direct application of feed on the litter and an average concentration of 1.3 × 10 4    Aspergillus cfu/g of wood shavings were incriminated in an outbreak of aspergillosis affecting a broiler breeder flock [3]. The sporadic use of fresh sugarcane bagasse instead of traditional storage stacked bagasse was associated with up to 90% mortality in six flocks of young chickens on the Island of Barbados.…”
Section: Birds Exposure To Aspergillus Fumigatus In Poultry Confinmentioning
confidence: 99%
See 2 more Smart Citations
“…Removal of mouldy litter resulted in health improvement [16]. The direct application of feed on the litter and an average concentration of 1.3 × 10 4    Aspergillus cfu/g of wood shavings were incriminated in an outbreak of aspergillosis affecting a broiler breeder flock [3]. The sporadic use of fresh sugarcane bagasse instead of traditional storage stacked bagasse was associated with up to 90% mortality in six flocks of young chickens on the Island of Barbados.…”
Section: Birds Exposure To Aspergillus Fumigatus In Poultry Confinmentioning
confidence: 99%
“…Two outbreaks of omphalitis where the primary cause was A. fumigatus have been investigated in young turkeys [18]. In poultry farms, mortality rate may rise slightly [14] or increases suddenly, peaks during a few days, and then returns to initial state [2, 3, 1517, 89]. Respiratory signs include dyspnoea, gasping, hyperpnoea with panting, nonproductive coughing, wheezing, cyanosis [3, 14, 15, 17, 21], and sometimes nasal discharge [19].…”
Section: Natural Avian Aspergillosismentioning
confidence: 99%
See 1 more Smart Citation
“…There are only two articles available with the former pointing out aspergillosis associated death in white storks (Olias et al, 2010), and the latter describing the occurrence of aspergillus strains obtained by tracheal swabs in live animals (Garcia et al, 2007). In our country, although aspergillosis has been reported in poultry and waterfowl (Akan et al, 2002, Akkoc et al, 2009, Atasever and Gumussoy, 2004, Beyaz et al, 2008, it has not yet been reported in storks. Turkey is located both on migration routes of the storks through from North Europe to North Africa and it is one of their breeding grounds.…”
Section: Introductionmentioning
confidence: 91%
“…Hastalık ya kronik formda sporadik ya da akut formda epizootik olarak ortaya çıkar ve bütün evcil ve yabani memeli ve çok sayıda kanatlı hayvan türünde bildirilmiştir (1,8,24). Kanatlıların ilk mikotik hastalıklarından biri olarak 1813 yılında ilk kez bir deniz ördeğinde saptanmıştır (10).…”
Section: Introductionunclassified